The Cashless Payment Paradox in Sustainable Consumption Trends: Between Efficiency and Overconsumption - Fitriyani, Fitriyani; Afrizal, Yogi Hady (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the contradictory nature between the benefits and risks arising from the use of cashless payment systems in relation to sustainable consumption patterns in society. Employing a qualitative approach, this research seeks to explore in depth the contradictory aspects between the convenience offered by cashless payments and the principles of sustainable consumption, which emphasize environmental preservation. The research is centered in the city of Makassar. The findings reveal that cashless payment systems function as a double-edged sword: on one hand, they provide efficiency and ease in transactions; on the other hand, they carry significant, often hidden, risks of promoting overconsumption, especially in the absence of strong self-control and adequate systemic interventions in the use of such digital payment technologies. The implications of this research are expected to offer valuable insights for policymakers, business practitioners, and consumers on how to harness digital payment technologies to support more sustainable consumption patterns, while mitigating the risks of overconsumption that may be detrimental to both individuals and the environment.